(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Purpose: The aim of this study is to compare two different concurrent chemoradiotherapy regimes – weekly cisplatin and three weekly cisplatin along with standard external beam radiotherapy in advanced head and neck cancer. Procedures: 90 untreated patients of advanced squamous cell carcinoma of head and neck were randomized into three arms: Arm A (n=30) patients received inj cisplatin 30mg/m2 weekly along with radiation; Arm B (n=30) patients received inj. cisplatin 100mg/m2 on a three weekly basis with radiation; Arm C (n=30) received only radiation. Radiotherapy was delivered to a dose of 66 Gy to 70 Gy in conventional fractionation in telecobalt machine. Findings: Complete response rate is significantly higher in arm B compared to that of arm A and arm C. Major toxicitities include neutropenia, anaemia and mucositis. Grade 3 neutropenia, anaemia and mucositis were found in arm A and arm B. No grade 3 toxicity was found in arm C. There was no grade 4 toxicity in any arm. Conclusion: We conclude that concurrent chemoradiation produce better response compared to that of radiation only. Toxicities were also increased in concurrent regimes. Out of two concurrent regimes, three weekly regimes showed better response with slightly increased but manageable hematological toxicities. Hence, this regime can be considered as standard of care for advanced head and neck cancer. Key words: Advanced head and neck cancer; Concurrent chemo-radiation; weekly versus three weekly cisplatin. DOI: http://dx.doi.org/10.3329/bjo.v17i2.8847 BJO 2011; 17(2): 88-95